From skyrmions to Z2 vortices in distorted chiral antiferromagnets - Osorio, Santiago Antonio (2019)
Swirling topological spin configurations, known as magnetic skyrmions, are known to be stabilized by different mechanisms. In particular, in chiral ferromagnets with Dzyaloshinskii-Moriya interaction (DMI), they appear in a topological crystalline phase, termed the skyrmion crystal phase (SkX), for appropriate values of the external magnetic field. A similar phenomenon is present in the antiferromagnetic case for the Heisenberg triangular antiferromagnet (HTAF) with DMI. Here, the most striking feature is that the emergent topological phase consists of three SkX interpenetrated sublattices. On the other hand, the pure HTAF, being described by an SO(3) order parameter, can host Z2 vortices. This raises the fundamental question of whether both nontrivial structures are related. In this Rapid Communication we unravel a hidden connection between both topological entities by studying the HTAF with anisotropic DMI. To this end, we combine an effective field theory description, the Luttinger-Tisza approximation, and Monte Carlo simulations. We show that even a slight anisotropy in the DMI proves to be the key ingredient to deform the interpenetrated SkX structure and reveal a Z2-vortex crystal.